Physiological and nutritional responses of two pakchoi (Brassica chinensis) cultivars to different red-blue light ratios in controlled environment - Anum, Hadiqa; Wang, Yaqin; Li, Yangmei; Sun, Guoqing; Luo, Jie; Gruda, Nazim S.; Liu, Guangmin; Tong, Yuxin (Frontiers in Sustainable Food Systems, 2025)
There is a growing interest in cultivating pakchoi under controlled environment agriculture. However, research on establishing the ideal environmental conditions for growing pakchoi in plant factories remains insufficient. Therefore, in this study, we investigated the optimal red-to-blue light ratio for enhancing pakchoi plants’ nutritional quality and growth. Five light treatments (B, R2B1, R4B1, R8B1, and R) were employed in our study, while white light (W) provided by fluorescent lamps was served as the control. The cultivars used were ‘Jingguan No. 1′, a green pakchoi, and ‘Ziguan No. 1′, a red pakchoi. After 20 days of treatment application, we observed significant improvements in dry weight and leaf area in green and red pakchoi plants under treatment R. Specifically, dry weight increased by 14.8% in green pakchoi and 26.7% in red pakchoi, while leaf area increased by 41.8% in green pakchoi and 81.1% in red pakchoi compared to the control treatment. Additionally, treatment R2B1 promoted net photosynthetic rate (Pn) in red pakchoi plants and enhanced stomatal conductance (Gs), intercellular CO2 concentration (Ci), and transpiration rate (Tr) in both pakchoi varieties. Treatment R4B1 facilitated the accumulation of photosynthetic pigments in pakchoi cultivars. On the other hand, the control treatment was found to be more conducive to the accumulation of glucosinolate concentration (GSc) in both red and green pakchoi cultivars. Notably, the concentrations of vitamin C (Vc) and soluble sugar in green pakchoi plants under treatment R4B1 increased by 78.5 and 31.4%, respectively, compared with those under control treatment. Similarly, the concentrations of Vc, soluble sugar, and anthocyanin in red pakchoi plants under treatment R2B1 were increased by 31.6, 177.8, and 114.4%, respectively, compared with those under the control treatment. These findings indicate that different pakchoi varieties exhibit distinct responses to different light-quality combinations.